Autoimmune Bullous Diseases - Gönül, Müzeyyen; Çakmak, Seray (IntechOpen, 2018)
Autoimmune bullous diseases are a group of rare skin diseases characterized by intraepidermal and subepidermal bullae formations due to autoantibodies directed against the structural proteins of the epidermis or the dermal-epidermal junction. Early and correct diagnosis and adequate treatment of autoimmune bullous diseases are important as they cause morbidity and mortality in the affected patients. This book, which gives detailed information about autoimmune bullous diseases, has two sections and nine chapters with sixteen contributing authors. The first section describes the structure and tasks of desmosomes and basement membrane zone, which consist of the major antigens of skin integrity targeted by autoantibodies. The second section is about the epidemiology, etiopathogenesis, mucocutaneous, histopathologic and laboratory findings, and therapy of autoimmune bullous diseases.